Breakdown of magnetism in sub-nanometric Ni clusters embedded in Ag. (21st October 2015) - García-Prieto, A; Arteche, A; Aguilera-Granja, F; Torres, M B; Orue, I; Alonso, J; Barquín, L Fernández; Fernández-Gubieda, M L
Abstract: Downsizing to the nanoscale has opened up a spectrum of new magnetic phenomena yet to be discovered. In this context, we investigate the magnetic properties of Ni clusters embedded in a metallic Ag matrix. Unlike in Ni free-standing clusters, where the magnetic moment increases towards the atomic value when decreasing the cluster size, we show, by tuning the Ni cluster size down to the sub-nanoscale, that there is a size limit below which the clusters become non-magnetic when embedded in Ag. To this end, we have fabricated by DC-sputtering a system composed of sub-nanometer sized and non interacting Ni clusters embedded into a Ag matrix. A thorough experimental characterization by means of structural techniques (x-ray diffraction, x-ray absorption spectroscopy) and DC-magnetization confirms that the cluster size is in the sub-nanometric range and shows that the magnetization of the system is dramatically reduced, reaching only 38% of the bulk value. The experimental system has been reproduced by density functional theory calculations on Ni m clusters ( m = 1–6, 10 and 13) embedded in Ag. The combination of the experimental and theoretical analysis points out that there is a breakdown of magnetism occurring below a cluster size of six atoms. According to our results, the loss of magnetic moment is not due to Ag–Ni hybridization but to charge transfer between the Ni sp and d orbitals, and the reduced magnetization observed experimentally is explained on the basis of the presence of a narrow cluster size-distribution where magnetic and non-magnetic clusters coexist.